2015
DOI: 10.1016/j.spinee.2015.06.047
|View full text |Cite
|
Sign up to set email alerts
|

A non-randomized clinical trial to assess the impact of nonrigid, inelastic corsets on spine function in low back pain participants and asymptomatic controls

Abstract: This study demonstrates that lumbar function assessed by self-reported and objective measures does not worsen when nonrigid, inelastic bracing is used for short periods of time for those with, or without, back pain. These data add to the existing literature that suggests short-term use of nonrigid, inelastic bracing for acute LBP does not decrease spinal function when measured separately with subjective or objective tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…Fritz et al [67] found that significant immediate reduction in the instrumented L3 stiffness of patients with nonspecific LBP (n = 48) after 2 sessions of spinal manipulation was associated with ensuing clinically significant reduction in Oswestry Disability index (ODI) scores after 1 week. Specifically, a multivariate regression showed that an immediate posttreatment decrease in the L3 segmental stiffness is an independent predictor of improved ODI scores at 1 week after spinal manipulation [68].…”
Section: Relation Between Segmental Spinal Stiffness and Lbpmentioning
confidence: 99%
See 2 more Smart Citations
“…Fritz et al [67] found that significant immediate reduction in the instrumented L3 stiffness of patients with nonspecific LBP (n = 48) after 2 sessions of spinal manipulation was associated with ensuing clinically significant reduction in Oswestry Disability index (ODI) scores after 1 week. Specifically, a multivariate regression showed that an immediate posttreatment decrease in the L3 segmental stiffness is an independent predictor of improved ODI scores at 1 week after spinal manipulation [68].…”
Section: Relation Between Segmental Spinal Stiffness and Lbpmentioning
confidence: 99%
“…Different spinal stiffness-testing devices have been developed to enhance the reliability and accuracy of segmental spinal stiffness measurements. Although some devices have been tested on human lumbar spines ( Table 3) [63][64][65][66][67][68][69][70][71][72], others are tailored for examining human cervical [73] or animal spines [74][75][76]. Overall, these devices can be classified into mechanical and mechanically assisted devices.…”
Section: Overview Of Instrumented Lumbar Stiffness Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…With recent advances in technology, clinicians can use reliable novel objective measurements (e.g., mechanical spinal stiffness assessments [302304], ultrasonic measurements of paraspinal muscles [305], advanced medical imaging [306, 307], or genetic analysis [308]) to examine patients at affordable costs. Given that age-related physical changes (e.g., sarcopenia or fatty infiltration of paraspinal muscles) in older adults may worsen LBP-related physical changes, the adoption of validated objective measurements may enhance the reliability and sensitivity in detecting physical deficits or monitoring posttreatment improvements of LBP in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на очевидный клинический эффект при использовании LSO в виде уменьшения выраженно-сти болевого синдрома, существует устоявшееся пред-ставление об опасности развития мышечной слабости и атрофии при его длительном применении [28,29,30]. В качестве возможных причин рассматривается непосредственное механическое воздействие ортеза на прилежащие мышцы [31].…”
unclassified